DANTES LITTERÆRE ATMOSFÆROLOGI - Brink, Dennis Meyhoff (K&K - Kultur og Klasse, 2013)
DANTE’S LITERARY ATMOSPHEROLOGY | The article argues that recent theories on affect and atmosphere by, for instance, Teresa Brennan, Lauren Berlant, and Peter Sloterdijk, can enter into an extraordinarily fruitful interchange with Dante’s Divine Comedy. On the one hand, these theories can direct our attention to the hitherto overlooked atmospheric phenomena that occur ubiquitously in Dante’s Comedy and provide us with concepts that render them legible as products of human emissions. On the other hand, the numerous descriptions of different atmospheres in Dante’s Comedy can contribute to overcoming the lack of linguistic specifications and distinctions which – according to theorists such as Brian Massumi and Peter Sloterdijk – characterizes today’s Western understanding of affective atmospheres and impedes its ongoing theorization. Based on readings of a selected number of atmospheres in Dante’s Comedy, the article argues that the Comedy not only anticipated insights that were not articulated theoretically until the twentieth and twenty-first century, but also makes up an exceptional encyclopedia of affective atmospheres that have not yet been examined, neither by Dante researchers, nor by theorists of affects and atmospheres. Therefore, both camps have much to learn from Dante’s literary atmospherology, which the article aims to make explicit.